Impact strength, fracture toughness and hardness improvement of PMMA denture base through addition of nitrile rubber/ceramic fillers - Alhareb, Ahmed Omran; Md Akil, Hazizan; Ahmad, Zainal Arifin (Elsevier, 2017)
Background/purpose: PMMA resin mostly used the fabrication of denture base by heatcuring technique. It has poor strength, including low impact strength and low fatigue resistance. In this work the combination of nitrile butadiene rubber (NBR) with two types of ceramic fillers (Al2O3 and YSZ, respectively) on the mechanical properties of denture base are investigated. Materials and methods: The denture base composites were fabricated by incorporating PMMA powder, 0.5 wt% of benzoyl peroxide (BPO), fixed at 7.5 wt% NBR particles and ceramic fillers (fixed at 5 wt%) as powder components. In total, 180 specimens were prepared for all tests and divided into 6 groups for each test (N= 10) coded G1–G6. Group 1 as the control group (without fillers) was mixed between PMMA powder and BPO; whereas the other five groups (G2–G6) were reinforced with NBR particles and different concentrations of ceramic fillers. The morphology of the fracture surface of specimens was examined by Field Emission Scanning Electron Microscopy (FESEM). Results: Statistical analysis, shows that the mean impact strength (IS) and fracture toughness (KIC) of control dentures when compared to reinforced PMMA at 7.5% NBR and 2.5% Al2O3/2.5% YSZ improved significantly (5.27± 0.21–10.25 ± 0.41 kJ/m2 and 1.60 ± 0.24–2.58 ±0.30 MPam1/2, respectively).